Analisis Perhitungan Daya Dukung Pondasi Footplate dengan Menggunakan PHP script - Ismail, M Rizky; Setyanto, Setyanto; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Foundation as we know is part of construction. A purpose of this construction is to continue a structure load to the ground which can endure the load without settlement effect. In order to guarantee the building is on stable condition concerning from structure load or outer force like a wind pressure, earthquake, etc and settlement which is more than permission limit unallowed. To avoid unfunctional foundation structure, foundation must placed on the solid ground which can endure sttructure load without causing excessive settlement. In this era computer technology develop quickly. Part of that is programming using PHP script. Programming using script can make some application to help us in our analyzing dan calculating proccess with interesting design , so we can operate it easily. And this program is using PHP script method . Basically analyzing and calculating footplate manually can used up our time. Because on calculating this we use a complex method, we need program to analyze and calculate footplate foundation. To make a calculation simpler and quicker. Some of manual test result which are found by us is having 1% difference with the program. So we consider this program is able to calculate the footplate foundation Keywords : foundation, footplate, PHP